Analytical engineering mechanics - Bose, Sujit K (Alpha Science International, 2012)
ANALYTICAL ENGINEERING MECHANICS contains a logically consistent, analytical development of mechanics (statics and dynamics), illustrated by a large number of examples of engineering interest. The exercises given at the end of each chapter are all partially solved. On studying the book, the reader will discover the underlying beauty of the subject, apart from learning the intricate engineering applications. The prerequisites of the book are the methods of Calculus, Differential Equations, Vector Algebra and elements of Vector Calculus. Calculus of Variations has also been used in an informal way. The book will be useful as a text book for undergraduate courses of engineering and mathematics and as a basic reference book on mechanics for scholars at higher levels.